Artificial Intelligence And Decision Making Processes In International Corporations - Abdul Hafid (Gudang Jurnal Multidisiplin Ilmu, 2025)
This paper explores the role of Artificial Intelligence (AI) in enhancing decision-making processes within multinational corporations. The primary issue addressed is how AI can be integrated effectively across diverse global markets, considering factors like regulatory frameworks, cultural diversity, and market dynamics. The research proposes a framework for AI implementation that ensures both operational efficiency and ethical soundness. The study employs a mixed-methods approach, combining qualitative interviews and quantitative surveys from key stakeholders in multinational corporations. Preliminary findings suggest that AI significantly improves decision-making speed and accuracy, particularly in data analysis, market trend prediction, and consumer behavior forecasting. However, challenges remain in adapting AI systems to various cultural and regulatory environments, highlighting the need for customization and local adjustments. This study contributes to understanding how AI can be applied more effectively and ethically across international markets, offering insights for future implementations in diverse business contexts.